Periodic UV-C light treatment for reducing the formation of free fatty acids in crude palm oil during storage - Said, Syahiddin Dahlan; Muslim, Abrar, Teuku Mainmun; Mel, Maizirwan (Penerbit Akademia Baru, 2020)
The formation of free fatty acids (FFA) during long term storage of crude palm oil (CPO) is inevitable, and it can reduce the quality and losing the CPO. Therefore, this study aims to evaluate the effect of UV-C light on lipase enzyme deactivation and the effect of periodic UV-C light treatment to reduce the FFA formation in the CPO during storage. The lipase deactivation was evaluated by exposing UV-C light to the lipase solution in the range of 2 to 8 hours at various dose rates of 0.8528, 1.2318 and 1.7238 (mW/cm2 ) and various periodic exposure times (2. 4 and 6 hours/day) for 7 to 28 storage days. The FFA level was analyzed using the NaOH titration method. The deactivation kinetics followed first-order model with deactivation rate constant in the range of 3.4 10-3 -5.8 10-3 min-1 . The half-life was 204.168, 150.586 and 120.024 (min) respectively. The highest value of FFA formation reduction is 85.6% at a dose rate of 1.7238 mW/cm2 and a periodic exposure time of 6 h/day for 28 days storage. Overall, the experimental results show that UV-C treatments were able to deactivate lipase enzymes and reduce the rate of FFA formation in CPO during storage